Problems of Categorizing and Explaining Party Systems in Africa - Gero Erdmann; Matthias Basedau (German Institute of Global and Area Studies (GIGA), 2007)
Starting from controversial findings about the relationship between party systems and the prospects of democratic consolidation, this article argues that problems can only be properly addressed on the basis of a differentiated typology of party systems. Contradictory research results do not pose an 'African puzzle' but can be explained by different and inadequate approaches. We argue that a modified version of Sartori's typology of party systems provides an appropriate method for classifying African party systems. Based on Sartori's framework, a preponderance of predominant and dominant party systems is identified. This can partly be explained by the prevailing authoritarian nature of many multiparty regimes in Africa as well as by the ethnic plurality of African societies. High ethnic fragmentation is not transformed into highly fragmented party systems. This phenomenon can be attributed to the most frequent 'ethnic congress party' which is based on an ethnic elite coalition. – – Die Parteienforschung zu Afrika hat bisher widersprüchliche Befunde zum Zusammenhang von Parteiensystem und zu den Aussichten für eine demokratische Konsolidierung hervorgebracht. Die widersprüchlichen Ergebnisse lassen sich zunächst mit unterschiedlichen und unangemessenen Ansätzen erklären. Zur Lösung des Problems ist jedoch eine differenzierte Parteiensystemtypologie notwendig. Zu einer sinnvollen Klassifizierung afrikanischer Parteiensysteme kann auf die Typologie von Giovanni Sartori zurückgegriffen werden, die allerdings modifiziert werden muss. Auf dieser Grundlage kann dann das Vorherrschen dominanter und prädominanter Parteiensysteme in Afrika identifiziert werden. Diese können im Wesentlichen mit zwei Faktoren erklärt werden: 1. mit dem autoritären Charakter vieler Mehrparteienregime und 2. mit der ethnischen Pluralität afrikanischer Gesellschaften. Entgegen mancher Erwartungen äußert sich die hohe ethnische Fragmentierung nicht in hoch fragmentierten Parteiensystemen. Dieses Phänomen beruht wiederum darauf, dass es sich bei den weitaus meisten Parteien in Afrika um 'ethnische Kongressparteien' handelt, die auf einer Koalition verschiedener ethnischer Eliten fußen.
Keywords: 300; Africa; South of Sahara; party systems; conceptual analysis; democratisation; electoral system; social cleavage; ethnicity